Effect of environmental data uncertainty in the framework of second generation intact stability criteria. (1st June 2022) - Bulian, Gabriele; Orlandi, Andrea
Abstract: The framework of second generation intact stability criteria in MSC.1/Circ.1627 includes a number of novelties for intact stability assessment. One of such novelties is the inherent possibility of designing a vessel for a specific operational area, by embedding area-specific environmental conditions. This is practically achieved through modification of the relevant calculation parameters in the criteria, on the basis of available MetOcean data. However, MetOcean data for a given area are generally available from multiple sources, and different sources provide information on environmental conditions on the basis of different approaches. This leads to a source-related variability that eventually reflects in the results of stability assessment, to an extent that is yet to be fully explored. The present study aims at providing quantitative indications in this respect. The Mediterranean Sea is considered as operational area, five different sources of MetOcean data are used, and level 1 and level 2-check 1 vulnerability criteria for parametric rolling are applied to two sample ships. The variability in the obtained safe zones of loading conditions is presented and discussed, also with reference to the effect of bilge keels. Some difficulties in the practical implementation of the procedure for embedding operational limitations are also highlighted and discussed. Highlights: Operational limitations according to second generation intact stability criteria. Two example cases using different sources of environmental data for Mediterranean Sea. Effect of MetOcean data uncertainty on safe zones from parametric roll assessment. Identification of some difficulties in the implementation of operational limitations. Operational limitations may be associated with reduced uniformity of application.